Masking Emotions: Face Masks Impair How We Read Emotions - Gori, Monica; Schiatti, Lucia; Amadeo, Maria Bianca (Frontiers in Psychology, 2021)
To date, COVID-19 has spread across the world, changing our way of life and forcing us to wear face masks. This report demonstrates that face masks influence the human ability to infer emotions by observing facial configurations. Specifically, a mask obstructing a face limits the ability of people of all ages to infer emotions expressed by facial features, but the difficulties associated with the mask's use are significantly pronounced in children aged between three and five years old. These findings are of essential importance, as they suggest that we live in a time that may potentially affect the development of social and emotion reasoning, and young children's future social abilities should be monitored to assess the true impact of the use of masks.